Combinatorial Click Chemistry Labeling to Study Live Human Gut-Derived Microbiota Communities - Hajjo, Haitham; Bhardwaj, Neerupma; Gefen, Tal; Geva-Zatorsky, Naama (Frontiers in Microbiology, 2021)
Gut microbes were shown to exert pivotal effects on health and disease. However, mechanistic studies of gut microbial communities are limited due to lack of technologies for real-time studies on live bacteria. Here, we developed COMBInatorial cliCK-chemistry (COMBICK) labeling on human gut-derived anaerobic bacteria to enable dynamic tracing of live, heterogeneous microbial communities on the strain level, including clinical isolates of the Enterobacteriaceae family. The number of labeled microbes that can be simultaneously differentiated grows exponentially depending on availability of fluorophores and machine capabilities. This method allows real-time studies of microbial communities in a variety of ecosystems, and can significantly advance mechanistic research in the microbiome field of study.